Analysis of Factors Responsible for Gender Gap in the Appointment of Vice-Chancellors in Universities in Nigeria - Kingsley Edinoh; ODILI, Chizoba Abigail; NWAFOR, Anthony Chijoke (Researchparks Publishing, 2023)
The paper looked at gender gap in appointment of the Vice-Chancellors in Universities in Nigeria. The paper employed both primary and secondary data. The secondary data were collected from print sources and online publications. The paper concluded by identifying low female academic representation in the appointment of University Heads (Vice-Chancellors) in Nigerian Universities. The paper identified cultural factors, poor implementation of gender policy on appointment of universities administrators; political influence, few female in the academia, low interest in leadership positions and weak institutions as factors that has contributed to low representation of female academics being appointed as Vice-Chancellors in Nigerian Universities. Based on these findings, the paper recommended that government should ensure gender policies are implemented in all the Universities in Nigeria in terms of appointments and selection of academic leaders especially Vice-Chancellors. Institutions established for ensuring gender equity should be strengthened with legislations to carry out their functions. Government should use social media and other socially accepted media to enlighten the populace and where it is expedient, challenge discriminatory gender norms, patriarchal practices, beliefs, early marriage practices and stereotypes that curtail girl education and female educational attainment in Nigeria.